Pengaruh Siskeudes, Kompetensi SDM Dan Transparansi Terhadap Kualitas Laporan Keuangan Dengan Pengendalian Internal Sebagai Variabel Intervening - Papra , Aldi Sujadin; Biana Adha Inapty (Politeknik Ganesha Medan, 2024)
Identifying the influence of Siskeudes usage, human resource competency (SDM), and transparency on the financial reports' qualities, using intervening variables that are internal controls was the goal of this research. The research adopts a quantitative approach. The subjects are all financial officers of villages within West Sumbawa Regency. Data collection employs a questionnaire with a population of 58 villages, using a total sampling technique that makes all population members sampled. Data analysis utilizes path analysis with the trimming method. This research concluded that: the usage of Siskeudes, human resource competency, and transparency partially and significantly affects the quality of financial reports, otherwise internal control doesn’t mediate the influence of Siskeudes usage on the quality of financial reports. On the other side, internal control mediates the influence of human resource competency on the quality of financial reports, and internal control mediates the influence of transparency on the quality of financial reports.